Pronunciation Teaching in English Language Classrooms in Saudi Arabia: Teachers’ Cognition and Practice - Ghazi Algethami; Hadeel Al Kamli (SAGE Open)
Research over the last two decades has shown that teaching pronunciation is both effective and important in language education. Nowadays, therefore, many English language textbooks include pronunciation activities. It is not clear yet how this has affected or changed teachers’ beliefs and practices in different teaching contexts. The current study examined English teachers’ beliefs and practices regarding pronunciation instruction in Saudi Arabia. Semi-structured interviews with Saudi teachers were conducted and analyzed in 2023. The teachers acknowledged the importance of pronunciation but had mixed opinions about how it should be taught, with most emphasizing the effectiveness of listening extensively to native input. Their teaching practice was limited to teaching the activities included in textbooks, which some described as insufficient for addressing their students’ needs. The teachers also mentioned they correct students’ pronunciation mistakes only when they affect intelligibility, with a primary focus on individual sounds. They reported prioritizing the teaching of other language skills over pronunciation due to limited class time and exams being focused on other aspects of language. The teachers unequivocally expressed the need for further training. Three areas of professional development were mentioned: a good knowledge base in phonetics, pronunciation teaching strategies, and English pronunciation. The present study concludes that pronunciation is still marginalized in English classrooms in Saudi Arabia, and teachers’ lack of training, as well as limited class time, play a role in this marginalization.